2005
DOI: 10.1007/s00253-005-0052-4
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetical approach to isolation of white-rot fungi capable of degrading polychlorinated dibenzo-p-dioxin

Abstract: A degradation experiment on PCDDs and phylogenetical analyses were carried out on newly isolated 2,7-dichlorodibenzo-p-dioxin (2,7-diCDD)-degrading white-rot fungi, strains BMC3014, BMC9152, and BMC9160. When these fungi were incubated with tri- or tetraCDDs, the substrates were degraded efficiently, and hydroxylated metabolites were detected. On the other hand, 1,3,6,8-tetrachlorodibenzo-p-dioxin was not decreased, and no metabolites were detected. Phylogenetic analysis of internal transcribed spacers (ITSs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…All mnp genes were closely related to the mnp genes described previously for P. radiata strain 79 (ATCC 64658) (8). Recently, phylogenetic analysis based on the internal transcribed spacer (ITS) region (containing 5.8S ribosomal DNA, ITS1, and ITS2) was carried out (11 MGmnp2 and MGmnp3 were classified as being typical MnP group I representatives (Fig. 3) (19).…”
Section: Discussionmentioning
confidence: 99%
“…All mnp genes were closely related to the mnp genes described previously for P. radiata strain 79 (ATCC 64658) (8). Recently, phylogenetic analysis based on the internal transcribed spacer (ITS) region (containing 5.8S ribosomal DNA, ITS1, and ITS2) was carried out (11 MGmnp2 and MGmnp3 were classified as being typical MnP group I representatives (Fig. 3) (19).…”
Section: Discussionmentioning
confidence: 99%
“…There is currently great interest in these fungi and their ligninolytic enzymes due to their potential for degrading and detoxifying recalcitrant environmental pollutants, such as polychlorinated dioxins (Kamei et al 2005), chlorophenols (Ehlers and Rose 2005), polycyclic aromatic hydrocarbons (Cambria et al 2008), and dyes (Asgher et al 2008). Furthermore, we recently demonstrated that ligninolytic enzymes such as manganese peroxidase (MnP) and laccase, which are produced extracellularly by white rot fungi, are effective in removing the estrogenic activities of nonylphenol (NP), bisphenol A (BPA), 4-tert-octylphenol, 17b-estradiol (E 2 ), ethinylestradiol, estrone, and genistein (Tsutsumi et al 2001;Suzuki et al 2003;Tamagawa et al 2005Tamagawa et al , 2006Tamagawa et al , 2007, and in degrading methoxychlor ) and the antifouling compound Irgarol 1051 (Ogawa et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Removal of dioxins by biological degradation is considered a feasible method as an alternative to other expensive physic-chemistry approaches [80]. Different dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) were studied for degradation by fungi such as Phlebia radiata I-5-6 [81,82,83], P. acerina, P. lindtneri and P. brevispora which can hydroxylate and methoxylate PCDDs [84], and Phanerochaete chrysosporium DSM 6909, P. chrysosporium DSM 1556, Irpex sp. W3, Trametes sp.…”
Section: Aromatic Hydrocarbonsmentioning
confidence: 99%